A theoretical reflection around the labor migrations, through historical case of the bracero program (1942-1964) - Albertí, Alfonsina Verónica (Nómadas. Critical Journal of Social and Juridical Science, 2013)
The present article tries to realise a reflection around as they have been the different factors that have been privileged to explain the phenomenon of the labor migration, from different theoretical positions, through the description of the labor migrations of Mexican to the United States within the framework of the denominated “Bracero program” in the temporary period that goes from year 1942 to year 1964.
Keywords: labor migration; Mexico; United States; bracero program